Impact of brief exposure to antifungal agents on the post-antifungal effect and hemolysin activity of oral Candida albicans - ELLEPOLA, Arjuna Nishantha; KHAJAH, Rana; JAYATILAKE, Sumedha; SAMARANAYAKE, Lakshman; SHARMA, Prem; KHAN, Zia (Journal of Applied Oral Science, 2015)
AbstractPost-antifungal effect (PAFE) of Candida and its production of hemolysin are determinants of candidal pathogenicity. Candida albicans is the foremost aetiological agent of oral candidosis, which can be treated with polyene, azole, and echinocandin antifungals. However, once administered, the intraoral concentrations of these drugs tend to be subtherapeutic and transient due to the diluent effect of saliva and cleansing effect of the oral musculature. Hence, intra-orally, Candidamay undergo a brief exposure to antifungal drugs.Objective Therefore, the PAFE and hemolysin production of oral C. albicans isolates following brief exposure to sublethal concentrations of the foregoing antifungals were evaluated.Material and Methods A total of 50 C. albicans oral isolates obtained from smokers, diabetics, asthmatics using steroid inhalers, partial denture wearers and healthy individuals were exposed to sublethal concentrations of nystatin, amphotericin B, caspofungin, ketoconazole and fluconazole for 60 min. Thereafter, the drugs were removed and the PAFE and hemolysin production were determined by previously described turbidometric and plate assays, respectively.Results Nystatin, amphotericin B, caspofungin and ketoconazole induced mean PAFE (hours) of 2.2, 2.18, 2.2 and 0.62, respectively. Fluconazole failed to produce a PAFE. Hemolysin production of these isolates was suppressed with a percentage reduction of 12.27, 13.47, 13.33, 8.53 and 4.93 following exposure to nystatin, amphotericin B, caspofungin, ketoconazole and fluconazole, respectively.Conclusions Brief exposure to sublethal concentrations of antifungal drugs appears to exert an antifungal effect by interfering with the growth as well as hemolysin production of C. albicans.